Communication: Gas-phase structural isomer identification by Coulomb explosion of aligned molecules - Burt, M; Amini, K; Lee, J; Christiansen, L; Johansen, R; Kobayashi, Y; Pickering, J; Vallance, C; Brouard, M; Stapelfeldt, H (AIP Publishing, 2018)
The gas-phase structures of four difluoroiodobenzene and two dihydroxybromobenzene isomers were identified by correlating the emission angles of atomic fragment ions created, following femtosecond laser-induced Coulomb explosion. The structural determinations were facilitated by confining the most polarizable axis of each molecule to the detection plane prior to the Coulomb explosion event using one-dimensional laser-induced adiabatic alignment. For a molecular target consisting of two difluoroiodobenzene isomers, each constituent structure could additionally be singled out and distinguished.